2016
DOI: 10.3389/fphar.2016.00321
|View full text |Cite
|
Sign up to set email alerts
|

Innovative Strategies to Develop Chemical Categories Using a Combination of Structural and Toxicological Properties

Abstract: Interest is increasing in the development of non-animal methods for toxicological evaluations. These methods are however, particularly challenging for complex toxicological endpoints such as repeated dose toxicity. European Legislation, e.g., the European Union's Cosmetic Directive and REACH, demands the use of alternative methods. Frameworks, such as the Read-across Assessment Framework or the Adverse Outcome Pathway Knowledge Base, support the development of these methods. The aim of the project presented in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…Predicting continuous endpoints can eliminate the discretization step of toxicity data, which requires endpoint-specific olds. 23 However, it was shown in another study that predicting exact values of continuous endpoints is harder than predicting binary categories. 14 Some multi-label classification methods, such as Random K labelset and label powerset, are not suitable for continuous endpoints.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Predicting continuous endpoints can eliminate the discretization step of toxicity data, which requires endpoint-specific olds. 23 However, it was shown in another study that predicting exact values of continuous endpoints is harder than predicting binary categories. 14 Some multi-label classification methods, such as Random K labelset and label powerset, are not suitable for continuous endpoints.…”
Section: Discussionmentioning
confidence: 99%
“…Developments have been made to create multi-label classification models using toxicity data sets such as the ToxCast data set, 15,16 Tox21 data sets, [17][18][19] Accelrys Toxicity Database, 20,21 and RepDose and ELINC data sets. 22,23 However, a recurrent problem in these studies, caused by missing labels in toxicity data sets, illustrated a major challenge in applying multi-label classification approaches to toxicity prediction. Toxicity profiles of some compounds are unknown across all toxicity phenotypes, either because such data are unavailable (e.g., compounds are not tested for all toxicity phenotypes), or it may be hard to find (e.g., being scattered in scientific literature).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Correlation analysis revealed that the predictivity was not influenced by the molecular weight of the active substances in the examined dataset. From a physiological point of view, dermal absorption is thought to decrease in particular when compounds larger than 500 g/mol are presented to the skin [34,35]. The examined dataset is restricted regarding the molecular weight range with only three compounds exceeding 500 g/mol.…”
Section: Additional Factors Influencing Absorptionmentioning
confidence: 99%
“…Since the review of Cronin et al (2013), a number of papers have appeared that focus on modern-day RA. Many of these, including Blackburn and Stuard (2014), European Chemicals Agency (ECHA) (2015), Organisation for Economic Co-operation and Development (OECD) (2015) and Schultz et al (2015), have put forward efforts to improve RA arguments and improve and innovate approaches (Batke et al, 2016;de Abrew et al, 2016;Shah et al, 2016;van Ravenzwaay et al, 2016). More recently, Ball et al, (2016) summarised the state-of-the-art surrounding read-across, along with reasons relating to regulatory non-acceptance, and compiled relevant guidance under the heading of "Good Read-Across Practice"; Hartung (2016) described the concept of linking different types of data and tools under the umbrella of good read-across practices.…”
Section: Introductionmentioning
confidence: 99%